RECONSTRUCTION OF DIVERSION CONCEPT IN CHILD PROTECTION OF CONFLICT WITH THE LAWS BASED ON THE VALUE OF JUSTICE - Ulina Marbun; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
A paradigm of punishment for children in Juvenile Criminal Justice System has been changing form retibutive approach toward restorative justice approach.. Diversion is used as an instrument of restorative justice impelementation, Diversion plays dominant role to fix the crime that has done by children. However, not all children have the right to receive diversion. There are the requirements to be applied. Article 7 (2) Law Number 11 of 2012 of Juvenile Criminal Justice System, establish the requirements are under 7 years imprisonment, and not a repetition. The requirements are not reflecting the theory of justice. Children who are threatened by imprisonment over 7 years would not have the right to get diversion. Then, success rate for implementation of diversion is low, it caused by law enforcer can not establish good communication among the parties. In addition, the implementation of diversion is taken place at the police station has contributed as factors of failure of the diversion. Framework in this study is the diversion has become the rights of every child in Juvenile Criminal Justice System, and definition of the diversion should be able to create a paradigm of restorative justice approach in the juvenile criminal justice system. The research method u in this study used doctrinal research method or normative research that study baout law which is drafted and developed by the basis of the doctrine. Based on the study that has been done, the application of diversion based on Law No, 11 of 2012 of Juvenile Criminal Justice System Children is unable to reflect the values of justice, it caused by the requirements, where the approach of restorative justice reflects the principle of justice, as intended by Aristotle in the theory of distributive justice and corrective justice. The conclusion of this research are: First, the protection of children in accommodated in the Law No. 11/2012 of Juvenile Criminal Justice System, but the concepts could not provide the protection in a holistic manner. Secondly, these obstacles (in implementation of diversion) because of culture (retibutive), although the juvenile criminal justice system has adobted teh restorative approach. Third, reconstruction of diversion must be built by the constructing diversion concept paradigm, so every child without exception has the rights to get diversion. Keyword: Divertion Concept, Child Protection, Juvenile Cryminal Justice System